Development of Learning Materials through CTL with Karo Culture Context to Improve Students’ Problem Solving Ability - Atania Christianti Ginting; Pargaulan Siagian; Edy Surya (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
The study aims to: 1) develop valid, practical, and effective quality learning materials for class VII SMP Berastagi 1 Program that focuses on the contextual teaching and learning model with the Karo cultural context (CTL-KCC); and 2) examine the enhancement of students' math problem-solving abilities as a side effect of using CTL-KCC learning materials. This research is development research using a 4-D development model consisting of four stages: define, design, develop, and disseminate. This research yielded learning materials such as learning implementation plans, student books, student worksheets, and mathematical problem-solving ability tests.The following conclusions were uncovered as a result of the research:1) In regards to their respective criteria, CTL-KCC learning materials had also met the valid, practical, and effective criteria.2) The N-gain value during the first trial of 0.30 for the "medium" criteria enhanced to 0.47 for the "moderate" criteria in the second trial, indicating an improvement in students' ability to solve mathematical problems using CTL-KCC learning materials.